Projection of holographic images in volumetric fluorescent fluids for near-eye displays - Makowski, Michal; Piątek, Paweł; Grynkiewicz, Mateusz (Photonics Letters of Poland, 2019)
The optical setup for holographic projection on the scatterings in fluorescent liquids is presented. Such media can be used as volumetric screens for near-eye holographic displays, solving the problem of speckle noise and very small exit pupils in existing setups. Three different oils (canola, olive and engine oil) with 532 nm laser and tonic water with 405 nm laser are used for projecting holographic fields, the quality of such images is investigated. The laser wavelength is cut out from acquisition on a camera and only filtered fluorescent light is observed. The best and brightest results are obtained with engine oil. Full Text: PDF References X. Li, C. P. Chen, H. Gao, et al. "Video-Rate Holographic Display Using Azo-Dye-Doped Liquid Crystal", Journal of display technology 10(6), 438-443 (2014). CrossRef X. Li, Z. Song, F. Li, X. Dong, W. Liu, "79‐3: Video‐rate Holographic Display in ZnSe layer‐assisted Quantum Dot Doped Liquid Crystal with High‐photorefractive Sensitivity", SID Symposium Digest of Technical Papers. Vol. 48. No. 1. 2017, CrossRef Sasaki, Takeo, et al. "Real-time dynamic hologram in photorefractive ferroelectric liquid crystal with two-beam coupling gain coefficient of over 800 cm–1 and response time of 8 ms", Applied Physics Letters 6(2) (2013) CrossRef N. Tsutsumi, K. Kinashi, A. Nomura, W. Sasaki, "Quickly Updatable Hologram Images Using Poly(N-vinyl Carbazole) (PVCz) Photorefractive Polymer Composite", Materials 5.8: 1477-1486 (2012) CrossRef M. Makowski, "Simple holographic projection in color", et al. Optics express 20.22: 25130-25136 (2012) CrossRef A. Yagi, M. Imura, Y, Kuroda, O. Oshiro, "360-degree fog projection interactive display", SIGGRAPH Asia 2011 Emerging Technologies. ACM, (2011) CrossRef C.H. Hsu, K. L. Hua, W. H. Cheng. "Omni-Tube: a low-cost portable omnidirectional interactive 3D display", SIGGRAPH Asia 2012 Posters. ACM, (2012) CrossRef Z. Zeng, H. Zheng, X. Lu, H. Gao, Y. Yu, "Dynamic holographic three-dimensional projection based on liquid crystal spatial light modulator and cylindrical fog screen", Opt Rev (2015) 22: 853 CrossRef I. Rakkolainen, "Feasible mid-air virtual reality with the immaterial projection screen technology", 3DTV-Conference, Tampere (2010) CrossRef S. Yanfeng, et al. "A multi-plane optical see-through holographic three-dimensional display for augmented reality applications", Optik 157: 190-196 (2018) CrossRef G. Li, D. Lee, Y. Jeong, J. Cho, B. Lee, "Holographic display for see-through augmented reality using mirror-lens holographic optical element", Opt. Lett. 41(11), 2486-2489 (2016) CrossRef C. L. Lin, Y. Z. Su, M. W. Hung, K. C. Huang "Augmented reality system", Proc. SPIE 7798, Applications of Digital Image Processing XXXIII, 779826 (2010) CrossRef A. Maimone, A. Georgiou, J. S. Kollin, "Holographic near-eye displays for virtual and augmented reality", ACM Trans. Graph. 36, 4, 1-16 (2017) CrossRef M. Quinten, Optical properties of nanoparticle systems: Mie and beyond (John Wiley & Sons 2010). CrossRef J.-W. Liaw, S.-W. Tsai, H.-H. Lin, T.-C. Yen, B.-R. Chen, "Wavelength-dependent Faraday–Tyndall effect on laser-induced microbubble in gold colloid", Journal of Quantitative Spectroscopy and Radiative Transfer 113(17), 2234-2242 (2012), CrossRef T. Mu et al. "Classification of edible oils using 532 nm laser-induced fluorescence combined with support vector machine", Anal. Methods 5, 6960 (2013) CrossRef T. Mu et al. "Classification of Motor Oil Using Laser-Induced Fluorescence and Phosphorescence", Analytical Letters 49:8, 1233-1239 (2015) CrossRef V. Rostampour, M. J. Lynch, "Quantitative Techniques To Discriminate Petroleum Oils Using LED-induced Fluorescence", WIT Transactions on Ecology and the Environment 95, 265 262 (2006) CrossRef F. Wyrowski and O. Bryngdahl, "Iterative Fourier-transform algorithm applied to computer holography", Opt. Soc. Am. A 5(7), 1058-1065 (1988) CrossRef